The Relationship Between Asset-Liability Management and Governance Quality in the Banking Industry - Kaufinger, Gregory G.; Neuenschwander, Chris (Journal of Accounting and Finance, 2024)
This study investigates whether governance quality is associated with asset-liability management (ALM) within the US banking industry. Based on stewardship theory, we hypothesize that there ought to be a significant, positive association between bank governance quality and a strong balance sheet due to inherent fiduciary responsibility and internal controls associated with an ALM governance process. Due to endogeneity concerns, we employ two-stage least squares regression and examine the relationship between 10 ALM metrics and governance risk scores (a component of ESG quality scores) for a cross-sectional sample of 251 US publicly traded banks in 2022. The results suggest that corporate governance influences ALM, not vice-versa. However, contrary to our hypothesized direction, favorable governance quality is associated with weaker ALM metrics as the results indicate that there is an inverse relationship between governance quality and ALM. Even so, the results provide evidence that bank governance quality is associated with balance sheet management. The results should be of interest to bank executives, regulators, investors, and other stakeholders in the banking industry.